The Effectiveness of Classical Tutoring Services Using Cinematherapy Techniques In An Effort To Provide Information Regarding Early Marriage To Students of SDN Duren Probolinggo - Elisabeth Christiana; Budi Purwoko; Wiryo Nuryono; Cintanaviola Vesciavingky Lalanda Ifnadya Arafa; Maryana Kamilah Octarine (Jurnal Pendidikan Anak, 2022)
This study aims to find out how effective classical guidance services are in providing information regarding early marriage to students of SD Negeri Duren, Probolinggo Regency. This research is a pre-experimental research, with one group pre-test – post-test design. Test the hypothesis using the Wilcoxon Signed Rank Test with the help of IBM SPSS statistics 25 for windows. Based on data analysis, the results obtained sig. 2 tailed by 0.012 which is less than 0.05. So it can be concluded that the hypothesis is accepted, that is, there is a difference in the use of the Classical Guidance service model with Cinematherapy techniques for SD Negeri Duren students in increasing information about the phenomenon of early marriage. This study shows that the use of the Classical Guidance service model with Cinematherapy techniques effective in increasing understanding of the phenomenon of early marriage in SD Negeri Duren, Probolinggo Regency.